Phenomenological description of a spin chain system with geometrical frustration of couplings - Zvyagin, A.A. (Физика низких температур, 2018)
The phenomenological model, using which we can in a relatively simple way calculate many magnetic, thermo-dynamic and dynamic characteristics of the spin chain material with the geometrical frustration of spin-spin couplings is proposed. The results of theoretical calculations well reproduce observed details of the low-temperature behavior of the magnetization, magnetic susceptibility, specific heat, magneto-acoustic characteristics, and some dynamical properties. In particular, the model permits to explain the double peak structure of the temperature dependencies of the magnetic susceptibility, specific heat, and the renormalization of the sound velocity, and can explain several features of the ESR frequency-field diagram.